2006
DOI: 10.1295/polymj.38.64
|View full text |Cite
|
Sign up to set email alerts
|

Wormlike Micelles of Pentaoxyethylene Tetradecyl Ether C14E5 and Hexaoxyethylene Hexadecyl Ether C16E6

Abstract: ABSTRACT:Micelles of pentaoxyethylene tetradecyl C 14 E 5 and hexaoxyethylene hexadecyl C 16 E 6 ethers in dilute aqueous solutions were characterized by static (SLS) and dynamic light scattering (DLS) experiments at several temperatures T between the LCST and UCST phase boundaries. The SLS results were successfully analyzed with the aid of the thermodynamic theory formulated with wormlike spherocylinder model for SLS of micelle solutions, yielding the molar mass M w of the micelles as a function of concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
44
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(58 citation statements)
references
References 18 publications
14
44
0
Order By: Relevance
“…Figure 8b shows that the length L w at fixed c significantly increases with raising temperature. This finding is in line with our previous results [1][2][3][4][5][6][7] for the micelles of the single surfactant C i E j . It is also in qualitative agreement with the results reported by Menge et al 23 for the C 12 E 5 + n-decane micelles and those by Kwon and Kim 31 for the C 12 E 5 + phospholipid micelles.…”
Section: Hydrodynamic Radius Of the Micellessupporting
confidence: 93%
See 2 more Smart Citations
“…Figure 8b shows that the length L w at fixed c significantly increases with raising temperature. This finding is in line with our previous results [1][2][3][4][5][6][7] for the micelles of the single surfactant C i E j . It is also in qualitative agreement with the results reported by Menge et al 23 for the C 12 E 5 + n-decane micelles and those by Kwon and Kim 31 for the C 12 E 5 + phospholipid micelles.…”
Section: Hydrodynamic Radius Of the Micellessupporting
confidence: 93%
“…The weight average molecular weight of the C 12 E 5 + n-dodecanol mixture calculated with a given w d was used as the surfactant molecular weight M 0 required in the theoretical analysis. 1=2 in the range of c examined, as in the case of the previous findings for the micelles formed with single surfactant of various type, [1][2][3][4][5]7 for those formed with binary C i E j mixtures, 8,9 and the C 10 E 5 micelles containing n-dodecanol. 18 These results are in good correspondence with simple theoretical predictions derived from the thermodynamic treatments of multiple equilibria among micelles of various aggregation numbers.…”
Section: Analysis Of Sls Datasupporting
confidence: 73%
See 1 more Smart Citation
“…[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] In the work, we have been able to determine the concentration-dependent characteristics of the micelles by separating contributions of the intermicellar thermodynamic and hydrodynamic interactions to the SLS and DLS results with the aid of the corresponding theories. We have determined the weight-average molar mass M w of the micelles as a function of surfactant mass concentration c along with the cross-sectional diameter d from the SLS data by using a molecular thermodynamic theory 21,38 formulated with the wormlike spherocylinder model.…”
mentioning
confidence: 99%
“…We have determined the weight-average molar mass M w of the micelles as a function of surfactant mass concentration c along with the cross-sectional diameter d from the SLS data by using a molecular thermodynamic theory 21,38 formulated with the wormlike spherocylinder model. It has then found that the molar mass M w dependence of mean-square radius of gyration hS 2 i, hydrodynamic radius R H , and intrinsic viscosity [] for the micelles of pure C i E j with various i and j [22][23][24][25][26][27][28] and their binary mixtures 29,30 is quantitatively represented by the chain statistical 39 and hydrodynamic theories [40][41][42][43] based on the wormlike chain and spherocylinder models, respectively. In particular, it has been demonstrated that the fuzzy cylinder theory [44][45][46][47] is favorably applied to analyze the apparent hydrodynamic radius R H,app , which is directly obtained from DLS experiment, as a function of the micelle concentration, thereby yielding the concentration-dependent micellar growth by separating contributions of the enhancement of hydrodynamic interactions among micelles with increasing concentration.…”
mentioning
confidence: 99%